Do Remittances Lead to Financial Instability? Evidence from Selected Asia–Pacific Countries - Akçay, Selçuk (Asian Journal of Applied Economics, 2025)
The Asia–Pacific region is among the top recipients of international remittances globally. This study examines the impact of remittances on financial instability and investigates whether the causal relationship between remittances and financial instability is symmetric or asymmetric in selected remittance-dependent Asia–Pacific countries: Pakistan, the Philippines, and Sri Lanka. Using the frequency domain causality approach and monthly data (Pakistan: 2005m01–2023m08; the Philippines: 1998m10–2023m08; Sri Lanka: 2015m01–2022m12), the results reveal both symmetric and asymmetric unidirectional causality from remittances to financial instability in Sri Lanka. In Pakistan, symmetric and asymmetric causality is observed from financial instability to remittances. No significant symmetric or asymmetric causal relationship is found in the Philippines. These findings suggest that recognizing asymmetric effects is essential for designing targeted policy responses in remittance-dependent economies. In particular, strengthening formal remittance channels, enhancing financial sector resilience, and using foreign exchange interventions in crisis-prone contexts like Sri Lanka can help mitigate remittance-induced instability.